2010
DOI: 10.3233/ch-2010-1305
|View full text |Cite
|
Sign up to set email alerts
|

Platelet morphological, functional and rheological properties attributable to addictions

Abstract: Hemorheological abnormalities such as elevated whole blood viscosity, plasma viscosity, erythrocyte deformability and platelet aggregation, hematocrit and fibrinogen levels, are frequently examined as diagnostic tool and prognostic relevance in socially important hemorheological disorders. Distinct biological -morphological and functional platelet alterations, have been described in different addictions (heroin-, cocaine-, nicotine-, alcohol-, etc.). Chronic addictions could cause biochemical and conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…27 Previous studies have shown that opioid addicts cause thrombocytopenia or thrombocytosis, and morphologic and functional changes in platelets. 10,11 However, in many studies investigating heroin addicts, although PLT count was found to be low compared with the control group, no statistically significant difference was reported. In our present study, PLT count was found to be lower than the control group and did not differ significantly.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…27 Previous studies have shown that opioid addicts cause thrombocytopenia or thrombocytosis, and morphologic and functional changes in platelets. 10,11 However, in many studies investigating heroin addicts, although PLT count was found to be low compared with the control group, no statistically significant difference was reported. In our present study, PLT count was found to be lower than the control group and did not differ significantly.…”
Section: Discussionmentioning
confidence: 98%
“…Opioid addiction is known to cause social and forensic problems as well as neuropsychiatric disorders, infectious diseases (acquired immunodeficiency syndrome, hepatitis B and hepatitis C), gastrointestinal diseases (stomach ulcers), cardiological diseases (arrhythmias and endocarditis), and a number of hematological changes (thrombocytopenia, leukocytosis and anemia) 6–9. Studies have shown that chronic opioid use causes thrombocytopenia or thrombocytosis, and morphologic changes in platelets such as degranulation, anisocytosis and cytoplasmic vacuolization 10,11. In addition, in vivo studies have been found that morphine activates platelet aggregation through α2-adrenoreceptor in platelets 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alcohol, smoking, and drugs can increase whole blood viscosity, red blood cell deformation, platelet aggregation, and alter hematocrit and fibrinogen levels. [79] The patient needs to develop a functional exercise program to execute well as an adjunct to treatment. Although patients have poor medical compliance with functional exercise, it has effectively reduced pain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Chronic drug use including opioid dependence may cause damage to platelets causing distinct morphological changes in platelets including reduction in number. [ 27 ] Thrombocytopenia is known to occur among active heroin users. [ 28 ] Previous studies have found a reduction in the platelets with longer duration of opioid use.…”
Section: Discussionmentioning
confidence: 99%